URINARY TRACT INFECTION CAUSED BY STAPHYLOCOCCUS SAPROPHYTICUS ISOLATED FROM ANIMAL - Rabab Jabbar Sekhi (Scholar Express Journals, 2022)
This study was carreid out to isolate Staphylococcus Saprophyticus from animals (cow , sheep) in AL-Shatraa city as causative agent of a urinary tract infection. ,observe their antibiotic sensitivity pattern and test their pathgensity in rats as model . To reach this goal 75 urine sample were gathered from animal (cow and sheep) with urinary tract infection in Thi-Qar city all these sample were cultured on different media (blood agar ,mannitol salt agar, nuterint agar) incubated in 37o C for 24 hours the isolates were diagonsed according to cultured and microscopic and many biochemical test, 14 isolate obtained (18.66%) ,the sensitivity of S.saprophyticus for antibiotic also tested and the result showed that the isolated S.saprophyticus highly sensitive to gentamcin (85.71%) and cefriaxone (78.57%) also most isolate were sensitive Ciprofloxacin with a percentage (71.42%) isolates. Other antibiotic sensitivity ranged from 64.28% to as low as 7.14%. The results of the pathogenesis study of S.saprophyticus in rats (after two day of injection of S.saprophyticus with a dose 240 colony forming unit in urethra ) showed acute histopathological change
Keywords: Staphylococcus Saprophyticus; pathogenesis